How the tennis court surface affects player performance and injuries - Barnett, T.; Pollard, G. (Medicine and Science in Tennis, 2007)
Data on the highest ranked men and women players indicates that players` performances are affected by the court surface. Players that perform best on the faster surfaces can be considered to be disadvantaged on the tour, due to the lack of grass court tournaments available. It would appear that the decrease in the number of grass court tournaments may have lead to an increase in the number of player injuries. It can be argued that the court surfaces used for the Masters Cup and the Olympic Games favour those players who prefer the particular surface selected for the event. For this reason, alternative methods of allocating court surface selection for these tournaments are suggested.